Exploring Linguistic Variation in Sawahlunto: A Analysis of Tansi Language Usage - Selvi Anelia Qubais; Refa Lina Tiawati; Wahyudi Rahmat; Vincent Oringo (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This research delves into the linguistic intricacies of Tansi, a regional language spoken in Sawahlunto, West Sumatra, Indonesia. Sawahlunto, a city with a rich cultural tapestry and complex social dynamics, serves as a fascinating case study for examining how language evolves and diversifies within a specific geographical context. This study investigates the variations in Tansi language, focusing on usage patterns and levels of formality, as influenced by the city's diverse population. Through a qualitative descriptive approach, the research meticulously documents and analyzes conversational data from various social settings, including interactions among students, market traders, and local youth. Data collection methods involved non-participatory observation and detailed audio recordings, allowing for a nuanced understanding of linguistic practices in situ. The findings reveal significant variations in Tansi language, shaped by both the context of use and the degree of formality required in different social interactions. Geographical diversity emerges as a critical factor driving these linguistic differences, as residents from various regions bring distinct linguistic influences into the local vernacular. This study not only sheds light on the dynamic linguistic landscape of Sawahlunto but also contributes to broader discussions on language variation and social interaction within regional communities. The research underscores the importance of considering geographic and social variables in the study of language, offering new insights into the complex mechanisms of linguistic adaptation and evolution in culturally rich environments.